Microbiological profile of diabetic foot infections and the detection of mecA gene in predominant Staphylococcus aureus - Ponmurugan Karuppiah; Suresh S. S. Raja; Muhammad Musthafa Poyil (Faculty of Medicine, Universitas Trisakti, 2022)
BACKGROUNDDiabetes mellitus (DM) is a serious health problem that is rapidly expanding worldwide. Staphylococcus aureus is a pathogenic bacterium which has a number of drug resistant strains. Different variants of this pathogen have been isolated from patients with diabetic foot ulcers - in persons having uncontrolled blood sugar level - all over the world, resulting in high rates of morbidity and mortality. The objective of this study was to determine the prevalence of drug resistant Staphylococcus aureus in diabetic foot infections (DFIs). METHODS An epidemiological survey was conducted and 300 pus samples were collected from wounds, abscesses, skin and soft tissue lesions of patients having type II diabetes with foot ulcer infections at a tertiary care hospital. Further, the antibacterial susceptibility patterns of all the isolated Staphylococcus aureus were determined against methicillin, oxacillin, vancomycin and novobiocin. RESULTS Pathogenic bacterial species including coagulase positive and coagulase negative Staphylococcus aureus, Escherichia coli, Klebsiella sp., Proteus sp., Pseudomonas sp., and Citrobacter sp. were identified, among which Staphylococcus was the main genus identified. A total of 13 (4.3%) isolates of coagulase positive Staphylococcus aureus were resistant to methicillin. Using PCR, 7 (53.8%) staphylococcal isolates were detected with the mecA gene. CONCLUSIONStaphylococcus aureus is the most common cause of DFIs. This study demonstrates that about 53.8% of all methicillin resistant Staphylococcus aureus isolates have mecA genes. Such a finding is the primary step in understanding and tackling the resistance mechanism.